Mergers and acquisitions, entrepreneurship and innovation - Weber, Yaakov; Tarba, Shlomo Y. (Technology, innovation, entrepreneurship, and competitive strategy series ;, 2016)
This volume of Technology, Innovation, Entrepreneurship and Competitive Strategy is devoted to research aimed at understanding success and failure factors of mergers and acquisitions in entrepreneurial firms. Research topics offer insights into the relationships of performance factors in all stage of M&As, such as planning, negotiation and post-merger integration. Contributions are multidisciplinary and cross-cultural, and tackle key issues from a variety of theoretical and empirical perspectives.